2015
DOI: 10.1016/j.jpainsymman.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Managing Medications During Home Hospice Cancer Care: The Needs of Family Caregivers

Abstract: Context Family caregivers (FCGs) are often at the frontline of symptom management for patients with advanced illness in home hospice. FCGs’ cognitive, social and technical skills in complex medication management have been well studied in the literature; however, few studies have tested existing frameworks in clinical cases in home hospice. Objectives This study sought to assess the applicability of Lau et al.’s caregiver medication management skills framework in the context of family caregiving in home hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
(47 reference statements)
0
34
0
1
Order By: Relevance
“…Although discharge summaries may underreport patient and family involvement, this observation suggests a missed opportunity to clarify the intentions of medication decisions and address questions and concerns regarding medication management. This finding is significant because previous studies reported that caregivers frequently feel overwhelmed and unprepared to manage hospice medications . Furthermore, although the rationale may be clear in the case of discontinuing many medications, providing clear and concise information regarding decisions to continue or initiate medications could enhance communication with hospice facilities and improve medication decision making around transitioning to hospice …”
Section: Discussionmentioning
confidence: 96%
“…Although discharge summaries may underreport patient and family involvement, this observation suggests a missed opportunity to clarify the intentions of medication decisions and address questions and concerns regarding medication management. This finding is significant because previous studies reported that caregivers frequently feel overwhelmed and unprepared to manage hospice medications . Furthermore, although the rationale may be clear in the case of discontinuing many medications, providing clear and concise information regarding decisions to continue or initiate medications could enhance communication with hospice facilities and improve medication decision making around transitioning to hospice …”
Section: Discussionmentioning
confidence: 96%
“…Medication that could be given as either a liquid or a pill also caused confusion for FCGs. 38 FCGs in another 41 study cited the sheer volume of medications as problematic. These often had to be given at specific times, with or without food, and in different combinations.…”
Section: Administrationmentioning
confidence: 99%
“…Indeed Lau et al 37 suggested that to understand and respond to patient need, a theme they refer to as personhood, FCGs must develop both symptom and medication knowledge (also see Ref. 38 ). Lau et al 37 classified symptom knowledge as encompassing the ability to recognize and respond to common symptoms at the end of life.…”
Section: Administrationmentioning
confidence: 99%
“…Caregivers may receive guidance and support in reducing or curtailing medications for disease management from hospice staff 1. However, most patients die in institutional settings, hospitals or nursing homes, where they are receiving care for the progression of one or more chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%